THE EFFECT OF MONOPOLY GAME AND TEACHER CREATIVITY ON CIVICS LEARNING ON EMPATHY ATTITUDES OF CLASS VD STUDENTS OF SD INPRES OESAPA KUPANG CITY - Vivi Eventi Soeki; Mintje Ratoe Oedjoe; Christine K Ekowati; Petrus Ly; Uda Geradus (Postgraduate School, Universitas Nusa Cendana, 2021)
This study aims to determine the effect of monopoly game media and teacher creativity on Civics learning on the empathy attitude of grade VD students of SD Inpres Oesapa, Kupang City. The subjects of this study were students of class VD SD Inpres Oesapa Kupang City, totaling 20 people. Sampling used was purposive sampling technique. Data collection tools used in this study were monopoly game media, teacher creativity and student empathy. These three variables use a Likert Scale consisting of 1 to 5 alternative answer choices, using a quantitative approach, while the analytical technique is statistical analysis with the data analysis method used is product moment correlation analysis. The results of the hypothesis test show that there is an effect based on the results of data analysis, a partial test for the Monopoly Game Media variable (X1) obtained a t-count value of 3.755 with a significance value of 0.002 0.05, then Ho is rejected and Ha is accepted, so that H1 (hypothesis 1 ) which reads